Solvolytic stereoselective coupling reaction of p-methoxyphenylmagnesium bromide with substituted allylic chlorides. - Lajis, Nordin Hj.; Khan, Mohammad Niyaz (Elsevier, 1992)
The α- and γ-coupling reactions of a few substituted allylic chlorides with p-methoxyphenylmagnesium bromide were concluded as to involve the formation of an intimate ion-pair intermediate. The solvents used gave substantial effects of both on the regio- and stereo-selectivity of the reaction.